Pengembangan Sistem Informasi Manajemen Klinik Kecantikan Dan Umum Berbasis Web (Studi Kasus: Praktik Mandiri Dokter Lina Malang) - Aida Fitri Nur Amrina; Nurudin Santoso; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The development of technology increasingly influences every aspect in the life of modern society today, which can be felt. Basically, technology is presented to facilitate the activities that have been done so as to increase the efficiency of time which is quite significant. One technology that is very familiar is the website. And the website itself is not only limited to providing the information sought but can also be used to manage existing data so that it can produce information. When we discuss about data processing it must be very closely related to Systems Information Management (SIM), a lot of data that we can process on SIM as in business and health aspects. In the aspect of health that can take care of patient data, patient history data, drug inventory data, as well as the most inherent in processing health data is medical data record. In the case study of the Independent Clinic Doctor Lina, which is a clinic that serves general problems and there are also beauty problems. In carrying out the activity of registration, patient queuing system, examination and management of products and clinical medicine, this method still uses conventional methods or by writing it down in a paper which is stored as book archives for each type of activity. This problem can greatly slow down the performance of the clinic because the number of patients visiting will continue to increase in proportion to the running time so the data that needs to be stored will also increase and become more complex. So that from the problems that arise from the clinic will be built a system that is capable of processing data contained in the clinic such as patient personal data, patient medical record data, patient visit data, disease data, as well as logistical data such as beauty products and medicines. Where later all the data stored in this system will be able to occur integrated in every part of the activities in the clinic as well as data accessed by many actors in the same place and time by creating a website-based of clinical management information system.